The role of human resource management in improving employee performance - Alwi, Muhammad; Setiawan, Nashrulloh Ari; Budiman, Sigit; Alika, Natasya Tiara (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to evaluate the impact of the role of human resource management on improving employee performance at PT. Agro Hikmah Sejahtera Nguling Pasuruan. The focus of the study is focused on the company and the evaluation of human resource management in the company from the point of view of management economics. This research uses a qualitative approach by applying literature research methods, interviews, and documentation analysis conducted at the research site. Data were analyzed to assess the extent to which the role of human resource management contributed to improved employee performance. The results showed that the role of human resource management has a significant impact in improving employee performance. In addition, the study identifies methods and strategies that can be used to improve employee performance through human resource management roles. From the perspective of management economics, this study provides an overview of the evaluation of human resource management.